RESULTS OF THE CLINICAL TRIAL FOURIER. NEW OPPORTUNITIES FOR TREATMENT OF VERY HIGH CARDIOVASCULAR RISK PATIENTS - Advisory Board (Российский кардиологический журнал, 2017)
Advisory Board of Russian Society of Cardiology (RSC), Russian National Atherosclerosis Society (RNAS), Russian Society of Cardiosomatic Rehabilitation and Secondary Prevention (RSCRSP)